Intramolecular TaqMan probes for genetic analysis. - Solinas, A; Thelwell, N; Brown, T (2002)
Novel intramolecular TaqMan probes have been evaluated on the W1282X locus of the human ABCC7 gene and shown to be more efficient than traditional TaqMan probes.